Land Use and Industrial Sustainability—Sustainable Land Use—Introduction: Land Use and Sustainability: A Critical Introduction to the Chilean Forestry Context - Piderit, Andrea Pino; Rozzi Marin, Ricardo Roberto; Braun, Andreas Ch. (My University, 2025)
This chapter critically examines the interplay between land use and industrial sustainability, focusing on the Chilean forestry sector, providing the context to understand the relevance of the IECO Topic V—"Land Use and Industrial Sustainability". The present introduction chapter highlights the shortcomings of the 2030 Agenda for Sustainable Development, particularly regarding land degradation, soil health, land tenure, and indigenous rights. These aspects are crucial for promoting sustainable land use and social equity, yet they remain inadequately addressed in the Agenda. The chapter illustrates how political and economic factors have driven the expansion of the forestry industry in central Chile, leading to significant environmental impacts, including biotic homogenization due to the establishment of monocultures of fast-growing exotic species like Pinus and Eucalyptus. The authors advocate for a more nuanced understanding of sustainability that incorporates diverse definitions and dimensions, emphasizing the need for policies that balance competing land uses and respect indigenous land rights. By drawing on ecosystem principles, the chapter proposes strategies for achieving sustainable industrial practices that decouple economic growth from environmental degradation. Ultimately, it calls for a reevaluation of current practices and policies to foster a more equitable and sustainable future for both people and nature in Chile.